Congenital/Primitive Hydrocephalus: Classification, Clinical Aspects, and Rehabilitation Approach - Caltabiano, Giusi; La Cognata, Daria; Zanghì, Antonio; Falsaperla, Raffaele; Vecchio, Michele; Marino, Francesco; Palmucci, Stefano; Belfiore, Giuseppe; Basile, Antonio; Polizzi, Agata; Praticò, Andrea D. (Journal of Pediatric Neurology, 2024)
Hydrocephalus is a heterogeneous disorder of cerebrospinal fluid (CSF) flow that leads to abnormal enlargement of the brain ventricles. The prevalence of infant hydrocephalus is approximately one case per 1,000 births. Hydrocephalus occurs due to an imbalance between the production and the absorption of CSF. The causes of hydrocephalus secondary to CSF overproduction are papilloma of the choroid plexus and rarely diffuse hyperplasia of the villi. All the other hydrocephalus forms are secondary to obstruction to normal CSF reabsorption and are also known as obstructive hydrocephalus. According to the location of obstruction, obstructive hydrocephalus can be defined as communicating, when caused by extraventricular obstruction of the CSF flow or decreased resorption of CSF distal to the fourth ventricle in the cisterns of the base or in the subarachnoid spaces, or as not communicating, in case of intraventricular obstruction to fluid flow. There is a third category, common in preterm infants, called external hydrocephalus which is secondary to delayed development of arachnoid function. Hydrocephalus leads to an increase in intraventricular pressure because of the lack of the mechanism regulating the homeostasis of the CSF flow. Increased intraventricular pressure is responsible for the clinical symptoms in affected child. Clinical presentation varies with age. In the neonatal period, prolonged or frequent apneic or bradycardic events, increasing head circumference, presence of sunsetting eyes or upward gaze palsy, evidence of full or tense anterior/posterior fontanelle, and splayed cranial sutures are signs of increased intracranial pressure. In infants, the most common signs are progressive macrocephaly, irritability, nausea/vomiting, headache, gait changes, and regression of developmental milestones. The extent of brain damage depends on the cause that led to hydrocephalus, the patient's age, and the rapidity of onset. The surgical treatment modalities consist of endoscopic ventriculostomy of the third ventricle and ventriculoperitoneal or ventriculoatrial CSF shunt.
Keywords: hydrocephalus; cerebrospinal fluid; papilloma; choroid plexus; communicating hydrocephalus; not communicating hydrocephalus